2016
DOI: 10.1371/journal.pone.0158232
|View full text |Cite
|
Sign up to set email alerts
|

Cell Size Critically Determines Initial Retention of Bone Marrow Mononuclear Cells in the Heart after Intracoronary Injection: Evidence from a Rat Model

Abstract: Intracoronary injection of bone marrow mononuclear cells (BMMNC) is an emerging treatment for heart failure. Initial donor cell retention in the heart is the key to the success of this approach, but this process remains insufficiently characterized. Although it is assumed that cell size of injected cells may influence their initial retention, no scientific evidence has been reported. We developed a unique model utilizing an ex-vivo rat heart perfusion system, enabling quantitative assessment of retention of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Increased initial retention was achieved due to the adhesive nature of fibrin, which enabled the MSC-dressing to firmly adhere to the heart, while securely retaining donor MSCs within. As such, leakage of donor cells early after transplantation, which is a major cause of poor donor cell engraftment using the current methods [ 7 , 8 ], were largely prevented. Since TachoSil Ⓡ is a prefabricated product, the fibrin concentration or crosslinking strength can be changed only marginally between conditions i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased initial retention was achieved due to the adhesive nature of fibrin, which enabled the MSC-dressing to firmly adhere to the heart, while securely retaining donor MSCs within. As such, leakage of donor cells early after transplantation, which is a major cause of poor donor cell engraftment using the current methods [ 7 , 8 ], were largely prevented. Since TachoSil Ⓡ is a prefabricated product, the fibrin concentration or crosslinking strength can be changed only marginally between conditions i.e.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important issues associated with MSC-based therapy for heart failure is the sub-optimal cell-delivery route [ 2 , 6 ]. While intramyocardial (IM) and intracoronary injections have been commonly used in both pre-clinical and clinical studies, these methods are known to result in poor donor cell engraftment [ 2 , [6] , [7] , [8] , [9] , [10] ]. In addition, these methods carry a risk of complications, such as arrhythmia occurrence and coronary embolism [ 7 , 9 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…72,73 Several comparison studies have claimed that AT-MSCs could achieve IC injection, 31 which is a predicted risk from animal models. 32 With regard to therapeutic efficacy, the majority of clinical studies have reported some clinical benefits of BM-MSC treatment, including reduced area of infarction, increased myocardial perfusion, decreased angina frequency, reduced hospitalization period, and clinical status. These favorable effects were observed not only in AMI and ICM patients, but also in nonischemic DCM patients.…”
Section: Adipose Tissue-derived Mscs (At-mscs)mentioning
confidence: 99%
“…Increased initial retention was achieved mainly by the unique nature of fibrin, which allowed the FG-MSC complex to firmly adhere to the heart, while securely retaining MSCs within. This feature attenuated the initial leakage of donor cells after transplantation, which is a major cause of the poor donor cell engraftment following IM and intracoronary injection 10 , 20 . Our in vivo results revealed that almost all transplanted MSCs were retained at 1 hour after FG-aided epicardial placement, while in contrast less than a half of donor cells were retained after IM injection of the MSC suspension.…”
Section: Discussionmentioning
confidence: 98%
“…This potentially induces ventricular arrhythmias due to disruption of electrical propagation within the myocardium and re-entry formation 7 , 8 . On the other hand, intracoronary injection carries the risk of coronary embolism, which is particularly critical when infusing MSCs into a diseased and narrowed coronary artery 6 , 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%